2012
DOI: 10.1152/jn.00407.2012
|View full text |Cite
|
Sign up to set email alerts
|

Does visually induced self-motion affect grip force when holding an object?

Abstract: Bringoux L, Lepecq JC, Danion F. Does visually induced self-motion affect grip force when holding an object?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…A visually induced effect on precision grip was not elicited despite their ability both to record precision grip with great accuracy and to induce compelling apparent up-down oscillation in their subjects. Our finding that subjects during experienced self-rotation and displacement did not sense the rod as exerting a centrifugal force on their hand is in accord with that of Bringoux and colleagues (Bringoux et al, 2012).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…A visually induced effect on precision grip was not elicited despite their ability both to record precision grip with great accuracy and to induce compelling apparent up-down oscillation in their subjects. Our finding that subjects during experienced self-rotation and displacement did not sense the rod as exerting a centrifugal force on their hand is in accord with that of Bringoux and colleagues (Bringoux et al, 2012).…”
supporting
confidence: 93%
“…After 20 perturbed reaches adaptation was approximately 80% complete. It is possible that the effects observed by Dvorkin, et al, 2009 would be even larger if practice trials were not given. Bringoux and colleagues explored whether an object held in a pincer grip at a seated subject’s lap would show systematic anticipatory grip compensations for visually induced oscillatory vection in the absence of real motion (Bringoux et al, 2012, White et al, 2020). Such anticipatory adjustments of grip force rapidly develop during actual exposure to up-down oscillatory motion.…”
mentioning
confidence: 99%
“…To date, it is still widely believed that self-motion perception is determined by characteristics of sensory receptors, and it has been shown that vection induces subtle sensorimotor changes in arm movement control (Bringoux et al, 2012). Interestingly, self-motion perception can be modulated by high-level visual input like seeing another person in motion (Lopez et al, 2013, see Deroualle and Lopez, 2014, this issue, for a review on vestibular information in social cognition).…”
Section: Spatial Cognitionmentioning
confidence: 99%
“…There are many examples in the literature of the dissociation between perception and action during the grasping (Aglioti, DeSouza & Goodale 1995, Haffenden, Schiff & Goodale 2001) and lifting of objects (Flanagan, Beltzner 2000, Bringoux, Lepecq & Danion 2012. The size-weight illusion affects the scaling of grip force in the first trials of a lifting task, but with repeated lifting movements the motor effect fades away, while the illusion persists (Flanagan, Beltzner 2000).…”
Section: Introductionmentioning
confidence: 99%